2016
DOI: 10.4314/agrosh.v16i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative economic analysis of irrigated and rainfed spinach (Amaranthus cruentus) production in Minna Metropolis, Niger State, Nigeria

Abstract: The study examined the comparative economic analysis of irrigated and rainfed spinach (Amaranthus cruentus) production in Minna metropolis, Niger State, Nigeria. Data were obtained from 120 randomly selected farmers using the purposive sampling technique. Production function model was used in the analysis of the data. The result showed that labour and farm size are the significant variables that influence spinach production output under the rainfed condition. On the irrigated scenario, labour, quantity of orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Increase in moisture regimes also increased plant height significantly. This is in agreement with the findings of El-Mahdi and Ei-Amin (2008), Obalola et al (2016) who reported that mean plant height was increased by the application of different irrigation regimes. The height of plant is an important growth character directly linked with the productive potential of plant in terms of fodder, grains and yield.…”
Section: Effect Of N Fertilizer and Moisture Regimes On Growth Parame...supporting
confidence: 93%
“…Increase in moisture regimes also increased plant height significantly. This is in agreement with the findings of El-Mahdi and Ei-Amin (2008), Obalola et al (2016) who reported that mean plant height was increased by the application of different irrigation regimes. The height of plant is an important growth character directly linked with the productive potential of plant in terms of fodder, grains and yield.…”
Section: Effect Of N Fertilizer and Moisture Regimes On Growth Parame...supporting
confidence: 93%
“…Vegetable plant parts are either eaten fresh or prepared in a number of ways. Vegetables tend to have short production cycles, receive intensive labour but few purchased inputs and produce high yields with strong nutritional value (Obalola and Tanko, 2016). They support rural and urban populations both in terms of subsistence and income generation without requiring large capital investments.…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify the variables affecting the net income of palm kernel nut processing in the study area, multiple regression analysis was utilized. Obalola and Tanko (2016) state that the model is implicitly described as follows: Three functional forms was fitted to the data and the lead equation was chosen based on statistical and econometric criteria such as the coefficient off multiple determination R 2 value, the F value, significant variables and so on. Explicitly, the functional forms are expressed: The result revealed that majority of the palm kernel nuts processors were male with less than a quarter of the processors being female (Table 1).…”
Section: Multiple Regression Modelmentioning
confidence: 99%